2002
DOI: 10.1038/sj.bjc.6600437
|View full text |Cite
|
Sign up to set email alerts
|

Intratumoural and peripheral blood lymphocyte subsets in patients with metastatic renal cell carcinoma undergoing interleukin-2 based immunotherapy: association to objective response and survival

Abstract: The aim of the present study was to analyse lymphocyte subsets in consecutive peripheral blood samples and consecutive tumour tissue core needle biopsies performed before and during interleukin-2 based immunotherapy, and to correlate the findings with objective response and survival. Twenty-six patients with metastatic renal cell carcinoma were treated with low dose s.c. interleukin-2, interferon-α and histamine. A total of 250 blood samples and 62 core needle biopsies from 23 and 19 of these patients, respect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
38
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 25 publications
0
38
0
Order By: Relevance
“…Our tumour tissue analyses demonstrated only modest reduction in the number of proliferating tumour cells induced by IFN-a and IL-2, suggesting that immunotherapy reduces tumour size but has only limited effect on intrinsic tumour aggressiveness in vivo. We have previously demonstrated that localisation of CD4 þ , CD8 þ and CD57 þ lymphocytes to sites of tumour is a requisite for the response to therapy (Donskov et al, 2002a), thus hypothesising that the antitumour activity of IFN-a in vivo is primarily cellular immune mediated. This hypothesis is in accordance with previous in vitro findings (Kosmidis et al, 1992;Tsavaris et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our tumour tissue analyses demonstrated only modest reduction in the number of proliferating tumour cells induced by IFN-a and IL-2, suggesting that immunotherapy reduces tumour size but has only limited effect on intrinsic tumour aggressiveness in vivo. We have previously demonstrated that localisation of CD4 þ , CD8 þ and CD57 þ lymphocytes to sites of tumour is a requisite for the response to therapy (Donskov et al, 2002a), thus hypothesising that the antitumour activity of IFN-a in vivo is primarily cellular immune mediated. This hypothesis is in accordance with previous in vitro findings (Kosmidis et al, 1992;Tsavaris et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Whereas cellular immune effector mechanisms are considered to be the most important mediators of IL-2 antitumour activity (Rubin et al, 1989;Donskov et al, 2002a), IFN-a in addition (Kosmidis et al, 1992;Tsavaris et al, 1996;Donskov et al, 2002a) is considered to exert antiproliferative (Grander et al, 1997) and differentiationinducing effects on the tumour cells (Pfeffer et al, 1998). In vitro, a direct antiproliferative effect on renal tumour cells has been demonstrated for IFN-a (Nanus et al, 1990), whereas IL-2 has no direct impact on cancer cells (Rosenberg, 2001).…”
mentioning
confidence: 99%
“…The cytotoxic activity of the tumor-infiltrating lymphocytes mainly resides in the CD16 dim NK cell population that expresses CD94/NKG2A more strongly than the peripheral NK cells (Schleypen et al, 2003(Schleypen et al, , 2006. Moreover, the response to IL2 in RCC patients can be correlated with the extent of tumor infiltration by NK cells, showing NK cell importance in tumor control (Donskov et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, NK and T cells remain viable and responsive to interleukin-2 (IL-2) Asea et al, 1996). IL-2 has no direct impact on tumour cells (Rosenberg, 2001) but requires NK and T-cells for tumourlysis (Donskov et al, 2002a(Donskov et al, , 2004a. Thus, the addition of histamine may potentially improve the efficacy of IL-2.…”
mentioning
confidence: 99%